2019
DOI: 10.1002/cne.24773
|View full text |Cite
|
Sign up to set email alerts
|

Differential expression of secretagogin immunostaining in the hippocampal formation and the entorhinal and perirhinal cortices of humans, rats, and mice

Abstract: Secretagogin (SCGN) is a recently discovered calcium‐binding protein belonging to the group of EF‐hand calcium‐binding proteins. SCGN immunostaining has been described in various regions of the human, rat and mouse brain. In these studies, it has been reported that, in general, the patterns of SCGN staining differ between rodents and human brains. These differences have been interpreted as uncovering phylogenetic differences in SCGN expression. Nevertheless, an important aspect that is not usually taken into a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 56 publications
0
19
0
Order By: Relevance
“…These values are much higher than the ones found in the present work for the human CA1 (Table 1). Such huge differences in synaptic density between humans and rodents -together with the above-mentioned divergences in the morphology and distribution of pyramidal cells in the SP of CA1 (18), as well as differences in other anatomical, genetic, molecular and physiological features (18,(21)(22)(23)(24)(25)-further support the notion that there are remarkable differences between the human and rodent CA1. These differences clearly need to be taken into consideration when making interpretations in translational studies comparing one species to another.…”
Section: Synaptic Densitymentioning
confidence: 71%
See 2 more Smart Citations
“…These values are much higher than the ones found in the present work for the human CA1 (Table 1). Such huge differences in synaptic density between humans and rodents -together with the above-mentioned divergences in the morphology and distribution of pyramidal cells in the SP of CA1 (18), as well as differences in other anatomical, genetic, molecular and physiological features (18,(21)(22)(23)(24)(25)-further support the notion that there are remarkable differences between the human and rodent CA1. These differences clearly need to be taken into consideration when making interpretations in translational studies comparing one species to another.…”
Section: Synaptic Densitymentioning
confidence: 71%
“…This great extent of SP represents a major difference with the rodent brain and other species. Indeed, important variances can be observed in the hippocampal neuroanatomy of humans compared to rodents (1,(18)(19)(20)(21). In the rat hippocampus, SP is around five cell bodies thick and neuronal somata are densely packed, being SR the layer that contributes the most to the total CA1 thickness.…”
Section: Ca1 Structural Compositionmentioning
confidence: 99%
See 1 more Smart Citation
“…This great extent of SP represents a major difference with the rodent brain and other species. Indeed, important variances can be observed in the hippocampal neuroanatomy of humans compared to rodents ( Amaral and Lavenex, 2007 ; Benavides-Piccione et al, 2020 ; Duvernoy, 2005 ; Slomianka et al, 2011 ; Tapia-González et al, 2020 ). In the rat hippocampus, SP is around five cell bodies thick and neuronal somata are densely packed, being SR the layer that contributes the most to the total CA1 thickness.…”
Section: Discussionmentioning
confidence: 99%
“…A ground-breaking study (Raju et al, 2018 ) demonstrated that expression of SCGN by cortical GABAergic neurons during development originating from the caudal and lateral ganglionic eminence (CGE and LGEs) at mid-gestation is a feature of human but not the mouse. Furthermore, SCGN expression is developmentally regulated and peaks before birth (Raju et al, 2018 ) with a very low density of interneuron-like SCGN+ cells detected in the neocortex of adult human post mortem brain by immunohistochemistry (Gartner et al, 2001 ; Tapia-González et al, 2020 ). However, a much higher density of both cell body and neuropil staining is observed in the human hippocampal and parahippocampal formations (Attems et al, 2007 ; Tapia-González et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%